MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MELALUI AKTIVITAS SAINTIFIK DAN VISUALISASI - Setiono Setiono; Gina Nuranti; Mira Mariana Agustini (JURNAL PENDIDIKAN SAINS UNIVERSITAS MUHAMMADIYAH SEMARANG, 2020)
This class action research aims to improve student learning outcomes by implementing scientific activities and visualization of subject matter. Research subjects in this study were high school students of Muhammadiyah High School in Sukabumi City (n = 20). The instrument used in this study was a multiple choice test to measure student learning outcomes, student observation sheet activities and interviews. The research method is classroom action research. The results showed that there was an increase in student learning outcomes after the implementation of scientific activities and visualization. scientific activities and visualization of subject matter can learners construct knowledge so that student learning outcomes have increase.